Formation and Applications in Electronic Devices of Lattice-Aligned Gallium Oxynitride Nanolayer on Gallium Nitride - Chen, Junting (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.